Reduction of Molybdenum by Pseudomonas aeruginosa strain KIK-11 Isolated from a Metal-contaminated Soil with Ability to Grow on Diesel and Sodium Dodecyl Sulphate (Journal of Environmental Microbiology and Toxicology, 2017)
Recently, molybdenum is considered as an emerging pollutant for its extreme toxicity to spermatogenesis in some organisms. Bacterial molybdate reduction to colloidal molybdenum blue (Mo-blue) forms the basis for its bioremediation. Molybdenum-reducing Pseudomonas aeruginosa strain KIK-11 was screened for its potential to degrade hydrocarbons and detergents. Optimal molybdate reduction to Mo-blue in this strain was supported by pH between 5.8 and 6.0, temperatures between 25 and 34 oC, molybdate concentration between 30 and 40 mM and a critical phosphate concentration of between 5.0 and 7.5 mM. The isolate was able to survive and grow on SDS and diesel. However, these compounds did not support Mo-blue production. The best electron donor source facilitating molybdate reduction is glucose, followed by galactose, fructose and citrate respectively. The process was inhibited by heavy metals such as copper (II), mercury (II) and silver (I). The bacterium was able to grow and detoxify multiple toxicants, a novel feat that is important in bioremediation.
Keywords: molybdenum SDS, Diesel, Bioremediation, Pseudomonas aeruginosa